Automatic Adjustment Mechanisms in Asian Pension Systems? - Arbatli Saxegaard, Elif (IMF Working Papers; Working Paper ;, 2016)
Automatic adjustment mechanisms (AAMs)-rules ensuring that certain characteristics of a pension system respond to demographic, macroeconomic and financial developments, in a predetermined fashion and without the need for additional intervention-have been introduced in many OECD countries to tackle public pension schemes' deteriorating financial sustainability. Incorporating AAMs-in particular linking retirement age to life expectancy-can be an important part of pension reforms in Asia. If implemented early, AAMs could help prevent the need for sharp adjustments in the future, increase the predictability and inter-generational equity of pension systems and enhance confidence.